Chemical analysis of various layers forming a ferromanganese crust retrieved in the Pacific Ocean (VA 13/2 - 237KD) - G Friedrich; A Schmitz-Wiechowski (PANGAEA, 2022)
During Valdivia cruise VA 13/2 dredging brought exceptionnally thick Mn crusts on top of basalt. One of these deposits is 22 cm thick and consists of three main zones and numerous subzones and layers. On the basis of the macroscopically visible zoning pattern and the natural planes of separation between subzones or layers, chemical analyses were carried out for Mn, Fe, Ni, Cu, Co, and Ba by atomic absorption spectroscopy (AAS), U by delayed neutron activation analysis, and Ce and La by energy-dispersive X-ray analysis.